Satisfaction Level Among Patients Attending The Dental Out-Patient Department Toward Rendered Dental Health Services (Journal of Chittagong Medical College Teachers' Association, 2019)
Background: Patient satisfaction with dental care is an important aspect of the quality of care both in dental hospitals and academic institutions. This study highlighted the area of patients’ satisfaction level at institutional level with available treatment facilities. The objective of the study was to assess the patients’ satisfaction level attending at the dental outpatient department toward dental health services rendered at an academic institution. Materials and methods: This cross-sectional type of observational study was conducted in Dental Unit, Chattogram Medical College, Chattogram from January 2018- June 2018.All together 100 physically and mentally sound adult patients (Visited more than once) who gave consent were interviewed throughout the process at out- patients department using 7-item closed ended questionnaire which included socio-demographic details, appointment schedule, technical competency of dental services, hospital administrative efficiency, hospital set-up environment, dentist- patient interaction and cost-effectiveness by using “Likert Scale”. The data were analyzed using Statistical Package for Social Science (SPSS version 20) which converted to descriptive and inferential statistics and chi square test also done to see the association. Results: Among 100 adult patients 46% were male, 54% were female, 38% belonged to 26- 40 years age group and 9% were over 55 years. Patients with less than graduate or bachelor degree were more satisfied with dental health services (p=0.000) on the mean satisfaction measures by educational level and mean satisfaction score by educational level, on treatment offered was not painful was 2.16 .800 and mean score of satisfaction on dental instruments used were sterilized was 2.48 1.078. Satisfaction with the dentists’ performances showed 34% female were very satisfied regarding offered treatment was not painful, followed by dental assistance services 35% female respondents were very satisfied on dental staff’s friendliness. Hospital setup and administrative efficiency were followed respectively. On the other hand, 17% male respondents were very satisfied with cost of the treatment. Conclusion: Nevertheless, majority of the patients were satisfied with Dentist- Patient interaction, technical competency, hospital setup and environment, hospital administrative efficiency and cost effectiveness of dental services with additional room of improvements with hospital setup and environment are needed.JCMCTA 2018 ; 29 (2) : 28-34